Hybrid Clinical and Histopathological Pattern in Annular Lesions: An Overlap between Annular Elastolytic Giant Cell Granuloma and Granuloma Annulare? - Felipe Ladeira de Oliveira; Luisa Kelmer Côrtes de Barros Silveira; Alice de Miranda Machado; José Augusto da Costa Nery (Case Reports in Dermatological Medicine)
Annular elastolytic giant cell granuloma (AEGCG) is a rare granulomatous skin disease of unclear pathogenesis which belongs to the group of disorders in the skin and elastic fibers with similar clinical features of granuloma annulare (GA). This case report is intended to describe a rare hybrid pattern in histopathology demonstrating coexistence of AEGCG and GA. An endocrine disease, such as diabetes mellitus (DM), could contribute to the coexistence of both lesions, and this possibility must be included in the medical investigation.